Preparation and Characterization of BeO-Supported Feldspar Porcelain - Al-Nasrawy , Dunia K. M. (Iraqi Journal of Science, 2023)
Due to the specific characteristic of porcelain, the insertion of Beryllium oxide has been studied. The basic materials and quantities were selected carefully. In this work, porcelain containing 32 wt% feldspar, 24 wt% quartz and 44 wt% clay was synthesized and beryllium oxide (BeO) (1 wt.%, 3 wt.%, 5 wt% and 7wt%) were add. The basic and new composition porcelain powders were uniaxially compacted into standard samples dimensions and fired at various sintering temperatures, 1100°C, 1300°C, and 1450°C then held for 2 hour in a furnace.The effects of sintering temperatures and beryllium oxide content on mechanical, electrical and structural properties were studied. The increasing of sintering temperature on the basic porcelain leads to an enhancement in bulk density and compressive strength. Basic porcelain which suffering lower sintering temperature (1300°C) introduces higher dielectric constant values in contrast with that suffering higher temperature (1450°C). The addition of BeO to the basic porcelain leads to decrease the bulk density and compressive strength. Porcelain with lower sintering temperature introduces higher έ values in contrast with higher temperature. The FTIR measurement show the existence of absorption at 800 cm-1 which attributable to Si-O-Si symmetrical stretching vibration band in all prepared samples. Band near 780 cm-l is attributed to the vibration of a beryllium atom moving in a tetrahedron of fixed oxygen atoms, while the absorption bands in the region 400-1500 cm-1 are due to the Be-O stretching and bending vibrations.